Effectiveness of the Cunningham technique for shoulder dislocation reduction and its role in providing analgesia and muscle relaxation as an adjunctive method - Ugur, Fatih; Albayrak, Mehmet (Elsevier BV, 2024)
Shoulder dislocation, particularly anterior dislocation, is a common orthopedic injury often presenting in emergency care settings, characterized by significant pain and muscle spasms. Prompt reduction is essential to alleviate symptoms and restore function. The Cunningham technique employs gentle pulling and massage motions targeted at the muscles and has emerged as a promising method for reducing anterior shoulder dislocations. However, its reported success rates vary widely across studies, and questions remain regarding its efficacy, particularly in cases of failure. This study aims to evaluate the effectiveness of the Cunningham technique for reducing anterior shoulder dislocations and its potential role in providing analgesia and muscle relaxation as an adjunctive method.A retrospective study was conducted on patients presenting with acute anterior shoulder dislocation at a single center. Reduction using the Cunningham technique was performed initially, followed by the external rotation technique if unsuccessful. Procedural sedation and analgesia were administered if the reduction was still not achieved, and shoulder dislocation reduction was performed again through the external rotation method. The patients' VAS scores were recorded and evaluated the Cunningham technique's effectiveness in reduction and whether it increases the effectiveness of other techniques applied for reduction by lowering the VAS score, even in cases where it is not effective.A total of 61 patients were included in the study. The reduction was performed using the Cunningham technique in 34.4% (21/61) patients, the external rotation technique in 47.5% (29/61) patients, and the external rotation technique with PSA in 18% (11/61) patients. Significant differences were observed in the duration of hospital stay among the three techniques, with ER with PSA resulting in the longest stay. VAS scores showed significant improvements from initial presentation to post-reduction in all three groups. A significant decrease in pre-reduction VAS scores was observed during the transition from the Cunningham technique to other techniques.The Cunningham technique showed effectiveness in reducing anterior shoulder dislocations, providing analgesia, and muscle relaxation. It demonstrated favorable outcomes as an initial reduction technique, with the external rotation technique used as a subsequent option. Further studies comparing the success rates and complications of the Cunningham technique with other reduction methods are warranted to establish its role in clinical practice.
Keywords: Male; Adult; Massage; Adolescent; Shoulder Dislocation; Muscle Relaxation; Original Articles; Middle Aged; Young Adult; Treatment Outcome; Humans; Manipulation, Orthopedic; Female; Analgesia; Retrospective Studies; Pain Measurement; Aged